International Survey of Practice for Prophylactic Systemic Antibiotic Therapy in Hip and Knee Arthroplasty - Thomas Parsons; Jonathan French; Takeshi Oshima; Francisco Figueroa; Thomas Neri; Antonio Klasan; Sven Putnis (Antibiotics, 2022)
(1) Background: Prophylactic systemic antibiotics are acknowledged to be an important part of mitigating prosthetic joint infections. Controversy persists regarding optimal antibiotic regimes. We sought to evaluate current international antibiotics guidelines for total joint arthroplasty (TJA) of the hip and knee. (2) Methods: 42 arthroplasty societies across 6 continents were contacted and their published literature reviewed. (3) Results: 17 societies had guidelines; of which 11 recommended an antibiotic agent or antibiotic class (10—cephalosporin; 1—cloxacillin); 15 recommended antibiotic infusion within an hour of incision and 10 advised for post-operative doses (8—up to 24 h; 1—up to 36 h; 1—up to 48 h). (4) Conclusions: Prophylactic antibiotic guidelines for TJA are often absent or heterogenous in their advice.